2010
DOI: 10.1098/rspb.2010.0772
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the cellular response of Daphnia magna (Crustacea: Cladocera) to its bacterial parasite

Abstract: Linking measures of immune function with infection, and ultimately, host and parasite fitness is a major goal in the field of ecological immunology. In this study, we tested for the presence and timing of a cellular immune response in the crustacean Daphnia magna following exposure to its sterilizing endoparasite Pasteuria ramosa. We found that D. magna possesses two cell types circulating in the haemolymph: a spherical one, which we call a granulocyte and an irregular-shaped amoeboid cell first described by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 42 publications
4
57
0
Order By: Relevance
“…A possible pathway would be through reduced activity of phenoloxidase, a key immune component in Daphnia (Pauwels et al 2010) shown to be less present under pesticide exposure (Campero et al 2008). Further, carbaryl may weaken the carapax, the physical barrier of the host, and a major defence against parasite spores (Auld et al 2010). The idea of a decrease in carapax strength is supported by our microarray analysis, revealing a downregulation of gene fragments related to cuticle proteins under direct carbaryl exposure (Jansen et al unpublished observations).…”
Section: Mechanistic Base Of Resistance Costs and Interactions: Firsmentioning
confidence: 66%
“…A possible pathway would be through reduced activity of phenoloxidase, a key immune component in Daphnia (Pauwels et al 2010) shown to be less present under pesticide exposure (Campero et al 2008). Further, carbaryl may weaken the carapax, the physical barrier of the host, and a major defence against parasite spores (Auld et al 2010). The idea of a decrease in carapax strength is supported by our microarray analysis, revealing a downregulation of gene fragments related to cuticle proteins under direct carbaryl exposure (Jansen et al unpublished observations).…”
Section: Mechanistic Base Of Resistance Costs and Interactions: Firsmentioning
confidence: 66%
“…[1a], [1b]), our synthesis of molecular mechanisms suggests that two-step processes are likely common and perhaps ubiquitous (see also Auld et al 2010). Recent models have begun to explore such two-step processes when both steps are mediated by traditional qualitative infection matrices.…”
Section: Are Existing Matrices Sufficient To Capture Essential Featurmentioning
confidence: 96%
“…This is not the case for microsporidian infections, which infect the host by shooting-in a harpoon-like manner-a tube into the host tissue and forcefully injecting their cytoplasm directly into the host cell. Thus, no barrier defence seems to exist against microsporidians (Wittner and Weiss, 1999) and the host's degree of resistance seems determined by genetic polymorphisms at the level of its within-host cell immune system, which is likely much more complex than the apparently simple genetics of the Pasteuria attachment step (Auld et al 2010). Although Pasteuria resistance is also influenced by the host's immune system (Hall and Ebert, 2012), the immune system's overall role in explaining variation in resistance is much less because it encounters only those parasites that were able to pass the barrier defence, that is, that attached to and penetrated into the host.…”
Section: Discussionmentioning
confidence: 99%